Expedient Microwave-Assisted Synthesis of Novel 6-Substituted 5-Alkoxy(benzyloxy)-3,6-dihydro-2H-1,3,4-oxadiazin-2-ones - Geffken, Detlef; Hansen, Finn K.; Khankischpur, Mehdi; Mauz, Tobias; Meurer, Ronald (Synlett, 2012)
Novel 6-substituted 5-alkoxy(benzyloxy)-3,6-dihydro-2H-1,3,4-oxadiazin-2-ones have been prepared in good yields and very short reaction times by intramolecular cyclization of α-hydroxyhydrazonates in the presence of sodium ethoxide under microwave irradiation.
Keywords: hydrazonates; nitrogen heterocycles; cyclization; microwave-assisted synthesis; ring closure